2016
DOI: 10.3906/sag-1501-173
|View full text |Cite
|
Sign up to set email alerts
|

Role of FLT3 in the proliferation and aggressiveness of hepatocellular carcinoma

Abstract: Background/aim: Previously we showed that Fms-like tyrosine kinase (FLT3) changes its cellular localization upon partial hepatectomy, suggesting a role in liver regeneration. FLT3 was also shown to play an important function in cellular proliferation and activation of PI3K and Ras. Thus, we aimed to investigate the role of FLT3 in hepatocellular tumorigenesis utilizing in vitro and in vivo models. Materials and methods:We used Snu398 cells that express FLT3. We investigated these cells' in vitro proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Aydin et al [44] have reported that FLT3 was active and participatory in the proliferation response during progenitor-dependent liver regeneration in rats. The role of FLT3 in HCC tumorigenesis, proliferation, and invasion was demonstrated through the stable knockdown of FLT3 gene in the FLT3-expressing HCC cell line and the pharmacological inhibition of FLT3 kinase [45]. According to the Cancer Genome Atlas dataset [46], FLT3 gene expression level and copy number gain is associated with the low OS of patients with HCC, implying that FLT3 may play a key role in HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Aydin et al [44] have reported that FLT3 was active and participatory in the proliferation response during progenitor-dependent liver regeneration in rats. The role of FLT3 in HCC tumorigenesis, proliferation, and invasion was demonstrated through the stable knockdown of FLT3 gene in the FLT3-expressing HCC cell line and the pharmacological inhibition of FLT3 kinase [45]. According to the Cancer Genome Atlas dataset [46], FLT3 gene expression level and copy number gain is associated with the low OS of patients with HCC, implying that FLT3 may play a key role in HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…The previous results showed that the mRNA expression of FLT3 was decreased in 64% of patients with HCC because of the loss of gene copy number; however, patients with high FLT3 expression benefit from sorafenib, which improves prognosis [ 34 ]. Therefore, the high expression of FLT3 promotes the proliferation and migration of HCC [ 35 ], which may be the reason for the high expression of FLT3 in vitro.…”
Section: Discussionmentioning
confidence: 99%